New facility for calibrating retroreflectometers - Miller, C. Cameron (Research results digest (National Cooperative Highway Research Program), 2005)
"This digest announces the results of NCHRP Project 05-16, "National Calibration Facility for Retroreflective Traffic Control Materials." The research team (composed of C. Cameron Miller, Todd Heimer, and Edward Early, National Institute of Standards and Technology) established a center for the calibration of portable retroreflectometers used for measuring the retroreflectivity of pavement markings and signs"--P. [1].